The impact of pretransplant donor-specific antibodies on graft outcome in renal transplantation: a six-year follow-up study - David-Neto, Elias (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2012)
OBJECTIVE: The significance of pretransplant, donor-specific antibodies on long-term patient outcomes is a subject of debate. This study evaluated the impact and the presence or absence of donor-specific antibodies after kidney transplantation on short- and long-term graft outcomes. METHODS: We analyzed the frequency and dynamics of pretransplant donor-specific antibodies following renal transplantation from a randomized trial that was conducted from 2002 to 2004 and correlated these findings with patient outcomes through 2009. Transplants were performed against a complement-dependent T- and B-negative crossmatch. Pre- and posttransplant sera were available from 94 of the 118 patients (80%). Antibodies were detected using a solid-phase (Luminex®), single-bead assay, and all tests were performed simultaneously. RESULTS: Sixteen patients exhibited pretransplant donor-specific antibodies, but only 3 of these patients (19%) developed antibody-mediated rejection and 2 of them experienced early graft losses. Excluding these 2 losses, 6 of 14 patients exhibited donor-specific antibodies at the final follow-up exam, whereas 8 of these patients (57%) exhibited complete clearance of the donor-specific antibodies. Five other patients developed “de novo” posttransplant donor-specific antibodies. Death-censored graft survival was similar in patients with pretransplant donor-specific and non-donor-specific antibodies after a mean follow-up period of 70 months. CONCLUSION: Pretransplant donor-specific antibodies with a negative complement-dependent cytotoxicity crossmatch are associated with a risk for the development of antibody-mediated rejection, although survival rates are similar when patients transpose the first months after receiving the graft. Our data also suggest that early posttransplant donor-specific antibody monitoring should increase knowledge of antibody dynamics and their impact on long-term graft outcome.